Pengembangan Game Edukatif Berbasis Pendekatan Etnomatematika Pada Kebudayaan Jawa Timur - Andini Safitri; Sumartono Sumartono; Windi Setiawan (Lembaga Riset dan Inovasi Almatani, 2026)
Mathematics education in Indonesia continues to face serious challenges in improving the quality of learning and student achievement. This is based on the results of PISA (Program for International Student Assessment) in 2022 with a score of only 366. To address this problem, ethnomathematical approaches come as innovative solutions that bridge the gap between formal mathematics and societal culture. Therefore, interactive learning media is needed. This type of research is a development research that aims to determine the feasibility of an educational game in mathematics teaching. This educational game was developed with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The researcher conducted a trial at UPT SD Negeri 327 Gresik with a population of 26 students by providing a learning motivation instrument (pretest-posttest). The test results showed that the pretest-posttest score data met a significant level of >0.05, which means that the data was distributed normally (normality test). The results of the paired sample t-test showed that there was a difference in pretest and posttest scores, which met a significant level of 0.05, which is 0.001, which means that educational games based on the ethnomathematics approach can increase students' interest in learning.